2019
DOI: 10.17554/j.issn.2311-5106.2019.06.311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Arthroscopic Rotator Cuff Repair in Patients Aged 70 Years and Older

Abstract: AIM: The purpose of this study was to evaluate the outcome of arthroscopic rotator cuff repair in patients aged 70 years or older and report our results in terms of pain, range of motion, muscle strength, and functional outcome. MATERIALS AND METHODS: We performed retrospective data review and identified 97 shoulders (94 patients) of our interest with minimum 24 months of follow-up. All patients were evaluated with Visual Analogue Scale (VAS), Range of motion (ROM), Manual Muscle Strength, and Oxford Shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…This can be attributed to overuse of the shoulder, such as repetitive shoulder movements during performing domestic activities, or on the job like manual work such as construction workers and carpenters, which puts strain on the shoulder, stresses muscles and tendons, and results in tendons wear down and causing a tear. This finding agrees with Hattrup, (2018); Babhulkar, Ravikumar, Patil, Kumar, (2019), who out a study entitled "Clinical outcome of arthroscopic rotator cuff repair in patients aged 50 years and older" which reported that tendons lose its strength and flexibility over 40 years old. This makes the ligaments more prone to partial or full thickness tears, and older people are predisposed to complete tears, which can be associated with a higher risk of tendon degeneration and increased difficulty of repair.…”
Section: Table (1): Percentage Distribution Of Patients In Both Studi...supporting
confidence: 90%
“…This can be attributed to overuse of the shoulder, such as repetitive shoulder movements during performing domestic activities, or on the job like manual work such as construction workers and carpenters, which puts strain on the shoulder, stresses muscles and tendons, and results in tendons wear down and causing a tear. This finding agrees with Hattrup, (2018); Babhulkar, Ravikumar, Patil, Kumar, (2019), who out a study entitled "Clinical outcome of arthroscopic rotator cuff repair in patients aged 50 years and older" which reported that tendons lose its strength and flexibility over 40 years old. This makes the ligaments more prone to partial or full thickness tears, and older people are predisposed to complete tears, which can be associated with a higher risk of tendon degeneration and increased difficulty of repair.…”
Section: Table (1): Percentage Distribution Of Patients In Both Studi...supporting
confidence: 90%